Being human: The role of pluripotent stem cells in regenerative medicine and humanizing Alzheimer's disease models. (June 2015) - Sproul, Andrew A.
Abstract: Human pluripotent stem cells (PSCs) have the capacity to revolutionize medicine by allowing the generation of functional cell types such as neurons for cell replacement therapy. However, the more immediate impact of PSCs on treatment of Alzheimer's disease (AD) will be through improved human AD model systems for mechanistic studies and therapeutic screening. This review will first briefly discuss different types of PSCs and genome-editing techniques that can be used to modify PSCs for disease modeling or for personalized medicine. This will be followed by a more in depth analysis of current AD iPSC models and a discussion of the need for more complex multicellular models, including cell types such as microglia. It will finish with a discussion on current clinical trials using PSC-derived cells and the long-term potential of such strategies for treating AD.